2022
DOI: 10.3390/toxics10030127
|View full text |Cite
|
Sign up to set email alerts
|

The Recolonization Concentration Concept: Using Avoidance Assays with Soil Organisms to Predict the Recolonization Potential of Contaminated Sites

Abstract: In this study the recolonization concentration concept for soil organisms is presented and validated. This concept is based on the empirically deduced avoidance–recolonization hypothesis, which shows a negative correlation between avoidance (ACx) and recolonization (RCx) (ACx = RC100-x) responses. The concept was validated in a two-step approach composed by (i) individual placement tests, to demonstrate the non-influence of individual placement in a dual chamber avoidance test and (ii) small scale gradient tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Lukkari et al (2005), found that Aporrectodea tuberculata begins to avoid Cu-contaminated soil at around 50 mg/kg, and from 79 mg/kg onwards, the habitat limit threshold was exceeded. In a recent work by Renaud et al (2022), avoidance test results were expressed as contaminant concentrations (AC) that could limit 50 and 80% of the individuals, namely AC50 and AC80; in that work, it was found that the Cu AC50 and AC80 for Eisenia andrei in the tested soil were 49.5 mg/kg and 112 mg/kg, respectively. In the present study, already at 110 mg/kg of Cu contamination, 76% of earthworms avoided the soil (NR of 52%), while at 165 mg/kg, the avoidance reached 88% (NR of 76%).…”
Section: Avoidance and Reproductive Outputsmentioning
confidence: 99%
“…Lukkari et al (2005), found that Aporrectodea tuberculata begins to avoid Cu-contaminated soil at around 50 mg/kg, and from 79 mg/kg onwards, the habitat limit threshold was exceeded. In a recent work by Renaud et al (2022), avoidance test results were expressed as contaminant concentrations (AC) that could limit 50 and 80% of the individuals, namely AC50 and AC80; in that work, it was found that the Cu AC50 and AC80 for Eisenia andrei in the tested soil were 49.5 mg/kg and 112 mg/kg, respectively. In the present study, already at 110 mg/kg of Cu contamination, 76% of earthworms avoided the soil (NR of 52%), while at 165 mg/kg, the avoidance reached 88% (NR of 76%).…”
Section: Avoidance and Reproductive Outputsmentioning
confidence: 99%